Assessment of a Synthetic Steroid and Flutamide on Dopamine, GSH and H2O2 Levels in Rat Brain in Presence of Fructose - C. Guzman, David; Bratoeff, Eugene; S. Ortiz, Aylin; H. Garcia, Ernestina; O. Brizuela, Norma; B. Mejia, Gerardo; J. Olguin, Hugo; S. del Angel, Daniel; M. Cruz, Israel (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2014)
Flutamide is a drug used in the treatment of androgen-dependent disorders. However, this treatment is usually accompanied by some adverse side effects. The aim of this work was to analyse the effect of flutamide and to compare this effect with that of a synthetic steroid - 3β-propionyloxy-5-androsten-17-one (PPA) - on levels of dopamine and some oxidative stress markers. For this, thirty-six male young Wistar rats (65g) were recruited and divided into 6 groups. The groups were then treated as follows: Group 1 (control), dimethyl sulfoxide (DMSO); group 2, flutamide (4mg/kg); group 3, PPA; group 4, DMSO + fructose; group 5, flutamide + fructose; and group 6, PPA + fructose. The treatments were administered intraperitoneally at a daily dose of 4 mg/kg for 10 days. In the last day of treatment, blood samples were obtained and used to assess the levels of glucose and cholesterol. The animals were then sacrificed and their prostate gland and brains were obtained for measurement of 5α-reductase, glutathione (GSH), calcium, H2O2, and dopamine in cortex, hemispheres, and medulla/oblongata, using previously validated methods. Results: Dopamine levels decreased while GSH increased significantly in cortex and hemispheres of animals that received PPA plus fructose. Also in the same group, GSH decreased in cerebellum/medulla oblongata when compared with control group. Peroxidation decreased significantly in all tissues of the groups, while ATPase activity witnessed a significant decrease in cortex and an increase in hemispheres of animal groups treated with flutamide and PPA both in combination with fructose. Conclusion: The steroid, 3β-propionyloxy-5-androsten-17-one, may in part act as a neuroprotector mediated by the increase of GSH and decrease of H2O2. Besides, imbalance in steroid homeostasis may alter the metabolism of dopamine.
Keywords: oxidative stress